2018
DOI: 10.1186/s42077-018-0010-x
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of the incidence and causative pathogens of meningitis and surgical site infection after craniotomies for brain tumors in neurosugical ICU and ward: a cohort study

Abstract: Background: Postoperative meningitis and surgical site infections (SSI) is a challenging issue that may result in serious morbidity and mortality. This study aims at decreasing the incidence and identifying the causative pathogens of postoperative meningitis and SSI in patients undergoing craniotomies. Results: The study is a cohort study designed in ASA I and II patients undergoing elective craniotomies for brain tumors, to compare the incidence of meningitis and surgical sites infections between an intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Four individuals with more than one episode were classified as having "recurrent meningitis." (7) The results demonstrated that out of the 58 single episodes, the most common isolated pathogens were Staphylococcus aureus, Escherichia coli, Acinetobacter baumannii, and Pseudomonas aeruginosa. The remaining 9 percent accounted for mixed infections with pathogens that were Proteus mirabilis, Escherichia coli, Citrobacter diversus, and Staphylococcus aureus.…”
Section: Resultsmentioning
confidence: 96%
“…Four individuals with more than one episode were classified as having "recurrent meningitis." (7) The results demonstrated that out of the 58 single episodes, the most common isolated pathogens were Staphylococcus aureus, Escherichia coli, Acinetobacter baumannii, and Pseudomonas aeruginosa. The remaining 9 percent accounted for mixed infections with pathogens that were Proteus mirabilis, Escherichia coli, Citrobacter diversus, and Staphylococcus aureus.…”
Section: Resultsmentioning
confidence: 96%
“…An interesting finding in this study was that anaerobes, Acinetobacter spp, or Candida spp were not causes of SSI, differing from the findings of previous reports. 6,37,38 Antibiotic prophylactic therapy to prevent surgical site infections…”
Section: Microbiologic Etiology Of Surgical Site Infectionsmentioning
confidence: 99%